Kualitas Pelayanan Publik Bidang Administrasi Kependudukan Di Kecamatan Bogor Timur - Isdiyanti, Isdiyanti; Tjenreng, Muhammad Baharudin Zubakhrum (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
(Quality of Public Services for Population Administration in East Bogor Sub-district) The government as a provider of public services needed by the community must be responsible and continue to strive to provide the best service for the sake of improving public services. On the other hand, public satisfaction is a measure of the success of public services provided by public service providers. This study is a descriptive study using a qualitative approach to analyze the quality of public services in the field of population administration in East Bogor District. The data analysis technique used is an interactive model. The results of the study indicate that the quality of public services in the field of population administration in East Bogor District is seen from the aspects of physical facilities, reliability, responsiveness, assurance, empathy, namely the Public Service section in East Bogor District has not met adequate service facilities to provide services to the community. The community is satisfied with the services provided by the East Bogor District in terms of reliability regarding reliability in handling every public complaint. Employees who provide services to the community who are confused in needing public services, then the sub-district employees provide good service to the community, so that it is easier to obtain information and access to services provided by the government. This will minimize the convoluted bureaucracy and increase government productivity in providing services to the community. For security in the East Bogor District, it has shown efforts to improve the quality of its services related to providing a sense of security for the community. The empathy given by the East Bogor District is by giving a pleasant impression. Abstrak Pemerintah sebagai penyedia layanan publik yang dibutuhkan oleh masyarakat harus bertanggung jawab dan terus berupaya untuk memberikan pelayanan yang terbaik demi peningkatan pelayanan publik. Disisi lain kepuasan masyarakat adalah tolak ukur dari keberhasilan pelayanan publik yang diberikan oleh penyedia layanan publik. Penelitian ini adalah penelitian deskriptif dengan menggunakan pendekatan kualitatif untuk menganalisa kualitas pelayanan publik bidang administrasi kependudukan di Kecamatan Bogor Timur. Teknik analisis data yang digunakan adalah model interaktif. Hasil penelitian menunjukkan bahwa kualitas pelayanan publik bidang administrasi kependudukan di Kecamatan Bogor Timur dilihat dari aspek fasilitas fisik, kehandalan, daya tanggap, jaminan, empati yaitu bagian Pelayanan Umum di Kecamatan Bogor Timur belum memenuhi fasilitas pelayanan yang memadai untuk memberikan pelayanan kepada masyarakat. Masyarakat merasa puas dengan pelayanan yang di berikan Kecamatan Bogor Timur dalam aspek reliability mengenai kehandalan dalam menangani setiap keluhan masyarakat. Pegawai yang memberikan pelayanan kepada masyarakat yang confuse dalam membutuhkan pelayanan publik, maka pegawai kecamatan memberikan pelayanan yang baik kepada masyarakat, agar lebih mudah untuk memperoleh informasi dan akses ke layanan yang disediakan oleh pemerintah. Hal ini akan meminimalisir birokrasi yang berbelit-belit dan meningkatkan produktivitas pemerintah dalam memberikan layanan kepada masyarakat. Untuk keamanan di Kecamatan Bogor Timur sudah menunjukan upaya meningkatkan kualitas pelayanannya terkait memberikan rasa aman bagi masyarakat. Empati yang diberikan pihak Kecamatan Bogor Timur yaitu dengan memberikan kesan yang menyenangkan.